1996
DOI: 10.1023/a:1016005529420
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Elevated serum AAG impedes the transport of imipramine and desipramine into the brain. Further, in the presence of elevated serum AAG levels, imipramine and desipramine concentrations in the brain did not correlate with their respective concentrations in the serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…[32][33][34] According to the packing insert (Imipramine hydrochloride, Novartis Pharma, 2006, Tokyo, Japan), after oral dosing of 75 mg imipramine, the maximum plasma concentrations of imipramine and desipramine are 70 ng/ml (0.25 mM) and 29 ng/ml (0.11 mM), respectively. Although the plasma or brain concentrations of other psychotropic drugs are unknown, it can be speculated that the expected brain concentrations of fluoxetine, imipramine, and desipramine are comparable to or higher than the K i values (1-16 mM).…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] According to the packing insert (Imipramine hydrochloride, Novartis Pharma, 2006, Tokyo, Japan), after oral dosing of 75 mg imipramine, the maximum plasma concentrations of imipramine and desipramine are 70 ng/ml (0.25 mM) and 29 ng/ml (0.11 mM), respectively. Although the plasma or brain concentrations of other psychotropic drugs are unknown, it can be speculated that the expected brain concentrations of fluoxetine, imipramine, and desipramine are comparable to or higher than the K i values (1-16 mM).…”
Section: Discussionmentioning
confidence: 99%
“…Holladay et al studied steady-state kinetics of imipramine in transgenic mice expressing serum AGP levels about 9-fold elevated over normal. [38,39] It was found that of the many physiologic derangements experienced by cigarette smokers, possible elevation of serum concentrations of the acute-phase reactant a, alpha-1-acid glycoprotein (AAG) is of particular interest because AAG is a major binding protein for several basic drugs, including lidocaine, amitriptyline, verapamil, and perhaps others. [40] It is generally assumed that in plasma, acidic drugs are mainly bound to human serum albumin.…”
Section: Agp Drug Binding In Disease Statesmentioning
confidence: 99%
“…The most widely used methods involve high-performance liquid chromatography (HPLC) with UV detection [4,11,12,[14][15][16][17][18]. FL/NORFL levels can also be measured in biological samples using gas chromatography (GC) coupled with MS [21,22], flame ionization [23], electron capture [24,25] or nitrogen phosphorus detection [26].…”
Section: Introductionmentioning
confidence: 99%